Cover Volume 5, Issue 2, August 2023 - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Numerical Analysis Finite Element Method of Settlement on Soft Soil, Case Study: National Road of Bts. Kota Sidoarjo – Gempol KM 31+150, Porong, East Java Yopi Delfian, Mahendra Andiek Maulana, Dwa Desa Warnana & Apri Artoto Subsurface Analysis of National Road Bts. Sidoarjo City – Gempol Using Geophisycs Method and Geotechnical Tests Indriani Rety Habsari, Mahendra Andiek Maulana, Dwa Desa Warnana & Apri Artoto An Alternative For New Road Embankment At Belanti Ex-Plg Food Estate Area, Pulang Pisau Regency – 3 (Case Study: Sta. 4+600 – Sta. 4+910 (Segment 1) and Sta. 0+000 – Sta. 0+065 (Segment 2)) Darma Karya Dika, Noor Endah Mochtar & Riwanto Marbun Alternative Design of Drive Pile and Floating Foundation of Bridge Structure over Soft Soil (Case Study : Muara Tahai Bridge Sta. 0+100 Kabupaten Pulang Pisau, Center Kalimantan) Asrul Mariadi, Noor Endah Mochtar & Riwanto Marbun Alternative Studies Abutment Structure and Bridge Oprit on Soft Soil at Belanti Food Estate Area, Pulang Pisau Regency, Central Kalimantan (Case Study : Muara Tahai Bridge Sta. 0+100) Asrul Mariadi, Noor Endah Mochtar & Riwanto Marbun